2015
DOI: 10.3389/fpls.2015.00312
|View full text |Cite
|
Sign up to set email alerts
|

FocVel1 influences asexual production, filamentous growth, biofilm formation, and virulence in Fusarium oxysporum f. sp. cucumerinum

Abstract: Velvet genes play critical roles in the regulation of diverse cellular processes. In current study, we identified the gene FocVel1, a homolog of Fusarium graminearum VelA, in the plant pathogenic fungus F. oxysporum f. sp. cucumerinum. This pathogen causes the destructive disease called cucumber Fusarium wilt (CFW), which severely affects the production and marketing of this vegetable worldwide. Transcript analyses revealed high expression of FocVel1 during conidiophore development. Disruption of the FocVel1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Some virulence-related genes of F. oxysporum have been shown to impact hyphal proliferation and colonization, for example, the six1 protein, an effector secreted during colonizing, is required for virulence of Fol (Rep, Meijer, Houterman, van der Does, & Cornelissen, 2005). However, only a few genes, including fga1, fga2, and fgb1 encoding G-protein α and β subunits, respectively (Jain et al, 2002(Jain et al, , 2003(Jain et al, , 2005 and FocVel1 encoding a velvet protein (Li et al, 2015), have been identified as involved in Foc infection.…”
Section: Fragkiadakismentioning
confidence: 99%
“…Some virulence-related genes of F. oxysporum have been shown to impact hyphal proliferation and colonization, for example, the six1 protein, an effector secreted during colonizing, is required for virulence of Fol (Rep, Meijer, Houterman, van der Does, & Cornelissen, 2005). However, only a few genes, including fga1, fga2, and fgb1 encoding G-protein α and β subunits, respectively (Jain et al, 2002(Jain et al, , 2003(Jain et al, , 2005 and FocVel1 encoding a velvet protein (Li et al, 2015), have been identified as involved in Foc infection.…”
Section: Fragkiadakismentioning
confidence: 99%
“…Rhizosphere colonization by Pantoea agglomerans was influenced by purB gens [330]. Velvet genes (FocVel1) involved in biofilm formation in Fusarium oxysporum f.sp.cucumerinum [331]. Quorum-sensing genes esaI, esaR encoding AHL signal synthase regulates bacterial adhesion and biofilm development [246], while, cps genes governs structural functions for EPS synthesis [139,332] in P. stewartii.…”
Section: Biofilm Formation By Plant Pathogenic Microorganismsmentioning
confidence: 99%
“…Velvet genes involved in biofilm formation [331] Pantoea stewartii esaI, esaR Quorum-sensing regulation (AHL signal synthase) governs bacterial adhesion, biofilm development [246] cps Encodes the structural functions for EPS synthesis [139,332] Ralstonia solanacearum pilA Type IV pili for surface adhesion and twitching motility [251] Xanthomonas axonopodis exo or eps EPS biosynthesis and virulence [70] Xanthomonas campestris gumD Codes for a glucosyltransferase involved in pathogenicity [333] Xanthomonas citri subsp. citri gumB, galU, gumD Xanthan production [334,335] hrpM Periplasmic glucan biosynthesis [255] gumB, gumD, galU, hrpM, and sahH Biofilm formation [256] Xylella fastidiosa rpf Product of diffusible signaling factor (DSF) involved in quorum sensing, biofilm formation and transmission of X. fastidiosa from insect to plant [319] hxfA or hxfB Hemagglutinin gene involved in cell-to-cell aggregation, colony formation and biofilm maturation within the xylem vessels [336] VELMOUROUGANE ET AL.…”
Section: Focvel1mentioning
confidence: 99%
“…Foc can survive in soil and seeds for many years or even decades [6]. Hyphae of this pathogen penetrate cucumber roots, then spread to the vascular tissues and occludes the xylem vessels, and also produces a toxin to kill cells, which leads to wilting of the leaves or even the entire plant, until plant death occurs several days or weeks after infection [7,8]. FW is extremely difficult to be controlled and changes in the pathogenicity of Foc have led to the ineffectiveness of certain fungicides [9,10].…”
Section: Introductionmentioning
confidence: 99%